Assessment of Pinus sylvestris L. forests state near Krasnoyarsk (case study of the Karaul'noe forestry) - Evdokimova Lyudmila; Tatarintsev Andrey (E3S Web of Conferences, 2023)
The research was conducted in Pinus sylvestris L. stands near Krasnoyarsk (subtaiga zone). The aim of the study is to assess the current state of recreational pine forests. Research methods included detailed forest pathological examination on six research plots, assessment of recreational disturbance (digression stage) by the transect method, integral assessment of forest health, graphical and correlation analysis. Recreational disturbance of the studied pine forests corresponds to I-IV stages of digression. From 1 to 40% of ground on the research plots has been trampled down. The vitality spectra of forest stands are characterized by right-sided asymmetry; the proportion of weakened trees is high in severely disturbed pine stands. With an increase in the recreational stress, the state of pine forests worsens significantly, and the proportion of dead trees increases. The absence of a significant relationship between the average health index and the stock of dead wood indicates that trees mortality cannot be used as an indicator when assessing the current state of recreational pine forests, which is explained by wood debris removal. The relative growing stock of healthy trees (with no signs of weakening), however, is an informative indicator.